2018
DOI: 10.12933/therya-18-605
|View full text |Cite
|
Sign up to set email alerts
|

Predictive species distribution model of two endemic kangaroo rats from Mexico: Dipodomys ornatus and D. phillipsii (Rodentia: Heteromyidae)

Abstract: Predictive species distribution models (SDMs) allow identifying suitable areas for the conservation of populations of endangered species. Dipodomys ornatus and D. phillipsii are two Nearctic rodents endemic to Mexico that inhabit arid and semiarid environments. Endemic species have a restricted distribution, making it difficult to monitor their distribution and conservation status. Therefore, it is important to understand the interactions between these species and the environmental/ecological variables in thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Ecological niche models have often been used to model and project rodent distributions and niches, but a large proportion of these studies are restricted to species found in the Americas (Martínez-Salazar et al 2012;Bean et al 2014;Kubiak et al 2017;Flores-Zamarripa & Fernández 2018;Urbina-Cardona et al 2019;Pardi et al 2020). African rodents have also been studied using ENM techniques; Taylor et al (2015) showed that trends in the distribution of Afromontane rodents reflect changes in biomes predicted by past, present, and future climate scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Ecological niche models have often been used to model and project rodent distributions and niches, but a large proportion of these studies are restricted to species found in the Americas (Martínez-Salazar et al 2012;Bean et al 2014;Kubiak et al 2017;Flores-Zamarripa & Fernández 2018;Urbina-Cardona et al 2019;Pardi et al 2020). African rodents have also been studied using ENM techniques; Taylor et al (2015) showed that trends in the distribution of Afromontane rodents reflect changes in biomes predicted by past, present, and future climate scenarios.…”
Section: Discussionmentioning
confidence: 99%